A Design for an Urban Electricity Market to Reduce the Expansion of the Low Voltage Distribution Grid - Teske, Franz; Wittl, Iris; Funk, Felix; Fehrle, Adrian; Franke, Jörg (2021 IEEE Electrical Power and Energy Conference (EPEC), 2021)
The transition from a centralized to a decentralized energy system is driven by prosumers, i.e., private households who operate flexible decentralized energy systems (DES). The demand and supply peaks resulting from their volatile consumption and generation can lead to grid bottlenecks and thus make expensive grid expansion necessary. Therefore, various approaches to use the existing power grid more efficiently by controlling private DES are being researched. In this paper, we propose a smart market platform (SMP) that reduces the need for grid expansion and incentivizes prosumer participation. The SMP also avoids grid congestions in the short term and provides suitable investment incentives in the long term. We conduct a scenario analysis to demonstrate that even using limited grid infrastructure, energy demands can be met in most scenarios. Our results show that market-based and decentralized coordination of control measures to reduce grid expansion can achieve advantages over existing solutions. These include more efficient asset dispatch in the short term, long-term investment incentives and, integration of different DES as well as individual needs of prosumer